Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1051/vetres/2010028
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for methicillin-resistantStaphylococcus aureus(MRSA) infection in dogs and cats: a case-control study

Abstract: Risk factors for methicillin-resistant Staphylococcus aureus (MRSA) infection in dogs and cats were investigated in an unmatched case-control study. A total of 197 animals from 150 veterinary practices across the United Kingdom was enrolled, including 105 MRSA cases and 92 controls with methicillin-susceptible S. aureus (MSSA) infection. The association of owners and veterinarian staff with the human healthcare sector (HCS) and animal-related characteristics such as signalment, antimicrobial and immunosuppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 48 publications
6
67
0
Order By: Relevance
“…Accordingly, the higher level of resistance to all antimicrobial agents amongst RVC isolates was not unexpected. Antimicrobial use has previously been shown to be the main driver for resistance in staphylococci isolated from pets (Holm and others 2002, Soares-Magalhães and others 2010, Weese and others 2012). Selection pressure from antimicrobial therapy is higher in isolates from animals referred to veterinary hospitals; in a recent North American study, referred dogs were 2.4 times more likely to have received antimicrobial therapy during the preceding 30 days than those admitted without referral (Baker and others 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the higher level of resistance to all antimicrobial agents amongst RVC isolates was not unexpected. Antimicrobial use has previously been shown to be the main driver for resistance in staphylococci isolated from pets (Holm and others 2002, Soares-Magalhães and others 2010, Weese and others 2012). Selection pressure from antimicrobial therapy is higher in isolates from animals referred to veterinary hospitals; in a recent North American study, referred dogs were 2.4 times more likely to have received antimicrobial therapy during the preceding 30 days than those admitted without referral (Baker and others 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The transfer of MRS between humans and animals has the potential to have a great public health impact (Cuny et al., 2010). It has been demonstrated that the studied samples from dogs and cats are much like those associated with hospital human strains (Magalhães et al., 2010). Therefore, the high occurrence of MRS (14.1% of the isolates) in the oral cavity of healthy cats is noteworthy and may represent a serious hazard to the public health.…”
Section: Discussionmentioning
confidence: 99%
“…Although S. aureus, including MRSA, is not the most common staphylococcal species isolated from dogs (Duquette and Nuttall 2004), in the last 5 years the number of reports of methicillin-susceptible S. aureus (MSSA) and MRSA-associated infections in dogs has grown rapidly (Abbott et al 2010, Aklilu et al 2010, Loeffler et al 2011. Several studies have reported risk factors associated with MSSA/ MRSA infections in dogs, including the previous use of antibiotics (Faires et al 2010), use of b-lactams or fluoroquinolones (Faires et al 2010), previous hospitalization (Soares Magalhã es et al 2010), surgical treatment (Tomlin et al 1999), and previous intravenous catheterization (Faires et al 2010). However, these studies were mainly focused on clinical cases.…”
Section: Introductionmentioning
confidence: 99%